2019
DOI: 10.3389/fnins.2019.00396
|View full text |Cite
|
Sign up to set email alerts
|

Use of Overlapping Group LASSO Sparse Deep Belief Network to Discriminate Parkinson's Disease and Normal Control

Abstract: As a medical imaging technology which can show the metabolism of the brain, 18F-fluorodeoxyglucose (FDG)-positron emission tomography (PET) is of great value for the diagnosis of Parkinson's Disease (PD). With the development of pattern recognition technology, analysis of brain images using deep learning are becoming more and more popular. However, existing computer-aided-diagnosis technologies often over fit and have poor generalizability. Therefore, we aimed to improve a framework based on Group Lasso Sparse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…Sivaranjini and Sujatha ( 2019 ) directly introduced the AlexNet model, which was trained by the transfer learned network. Shen et al ( 2019b ) proposed an improved DBN model with an overlapping group lasso sparse penalty to learn useful low-level feature representations. To incorporate multiple brain neuroimaging modalities, Zhang et al ( 2018b ) and McDaniel and Quinn ( 2019 ) both used a GCN model and presented an end-to-end pipeline without extra parameters involved for view pooling and pairwise matching.…”
Section: Applications In Brain Disorder Analysis With Medical Imagmentioning
confidence: 99%
“…Sivaranjini and Sujatha ( 2019 ) directly introduced the AlexNet model, which was trained by the transfer learned network. Shen et al ( 2019b ) proposed an improved DBN model with an overlapping group lasso sparse penalty to learn useful low-level feature representations. To incorporate multiple brain neuroimaging modalities, Zhang et al ( 2018b ) and McDaniel and Quinn ( 2019 ) both used a GCN model and presented an end-to-end pipeline without extra parameters involved for view pooling and pairwise matching.…”
Section: Applications In Brain Disorder Analysis With Medical Imagmentioning
confidence: 99%
“…The results are shown in Table 6. With the same training and test datasets, Shen et al (25) proposed a framework based on GLS-DBN to distinguish between PD and NC subjects. The classification accuracy achieved 90.0% in that study.…”
Section: A B Cmentioning
confidence: 99%
“…Eckert et al (24) combined visual assessment of individual scans with blinded computer assessment in the differential diagnosis of PD. Shen et al (25) improved a framework based on Group Lasso Sparse Deep Belief Network (GLS-DBN) to distinguish between PD and normal controls (NC) subjects based on FDG-PET imaging, and established the computer-aided classifier for PD and NC.…”
Section: Introductionmentioning
confidence: 99%
“…This study found that diagnostic power was lowest for any of these datasets alone, and that the greatest diagnostic power was obtained with combined [ 18 F]DOPA and metabolic datasets (AUC =0.98). One limitation of AI includes overfitting of data, Shen et al aimed to address this issue by adding the Group Lasso Sparse model to a Deep Belief Network (47). They applied their model to [ 18 F] FDG PET scans from 2 cohorts of PD and healthy control subjects, the first cohort was randomly divided into training, validation, and test datasets, while the second cohort was used only to test the model.…”
Section: Ai In Neurodegenerative Diseasementioning
confidence: 99%